Pengujian kebolehgunaan terhadap aplikasi mudah alih interaktif HAMZA di kalangan murid-murid prasekolah - Nur Amalina, Binti Shamsudin (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This study seeks to investigate the usability of interactive mobile applications HAMZA among preschool pupils. This study focuses on three main objectives: (1) to identify the effectiveness of interactive mobile applications HAMZA among preschool pupils; (2) to determine the efficiency of using an interactive mobile applications HAMZA among preschool pupils; (3) to identify the level of satisfaction with the use of interactive mobile applications HAMZA among preschool pupils. A total of six students in the Pasti Raudhatul Ilmi 1 involved as participant in this study. Smart phones and an interactive mobile applications HAMZA downloaded for free were used as an instrument for this study. The observation based on observation check list and interviews were conducted by researchers during the test session. The results showed that the main factors identified by researchers contributed to the success of preschool students complete the interactive mobile applications HAMZA game are (1) interaction of touch gestures exposure to preschool pupils; (2) smart phone ownership; and (3) the experience of playing the game.